2021
DOI: 10.1021/acsearthspacechem.1c00063
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Photosensitized Release of VOCs from Illuminated Seawater versus Freshwater Surfaces

Abstract: Recent studies have shown that photochemical reactions occurring at the air-water interface are a source of volatile organic compounds (VOCs) to the atmosphere. We report here the photosensitized formation of VOCs from illuminated freshwater and seawater mimics containing nonanoic acid (NA) and/or Suwannee River natural organic matter (SRNOM). Under an atmosphere of air, the total blank-corrected steady-state concentration of VOCs formed from illuminated seawater coated with nonanoic acid is somewhat smaller t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 93 publications
(283 reference statements)
0
10
0
Order By: Relevance
“…The authors propose three possible reasons: (1) differences in solubility of the products, (2) a decrease in the surface coverage of nonanoic acid on saltwater because of the elevated pH, and (3) interactions between nonanoic acid and the ions in saltwater. 425 These results are relevant to photochemical reactions at the surface of SSA with minimal organic content.…”
Section: Photochemistrymentioning
confidence: 91%
See 3 more Smart Citations
“…The authors propose three possible reasons: (1) differences in solubility of the products, (2) a decrease in the surface coverage of nonanoic acid on saltwater because of the elevated pH, and (3) interactions between nonanoic acid and the ions in saltwater. 425 These results are relevant to photochemical reactions at the surface of SSA with minimal organic content.…”
Section: Photochemistrymentioning
confidence: 91%
“…Although George and coworkers 422,424,425 have shown that it is possible for fatty acids to undergo direct photochemical reactions in highly concentrated surface lms, reactions are far more likely to proceed in the presence of a photosensitizer. 421 A good photosensitizer efficiently absorbs solar radiation and transfers energy to a less photochemically active species.…”
Section: Photochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…organic matter in seawater is implicated in HONO formation 33 and the release of VOCs. 34 The presence of surface-active organics can impact the oxidation of bromide by ozone. 35 Heterogeneous reactions involving chloride can change the speciation of gaseous oxidized mercury.…”
mentioning
confidence: 99%